Strengthening Civic Legal Literacy of PPKn Students Through Legal Learning - Indrawati Syamsuddin (Indo Publishing, 2026)
Legal learning in the Pancasila and Civic Education (PPKn) study program plays a strategic role in shaping students’ legal awareness as prospective civic educators. This study aims to reveal how the legal learning process contributes to strengthening the civic legal literacy of PPKn students at the Faculty of Teacher Training and Education, Universitas Halu Oleo. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews with ten PPKn students from the 2025 cohort, observation, and documentation study, then analyzed using the interactive model of Miles, Huberman, and Saldāña. The findings reveal five main themes representing the strengthening of students’ civic legal literacy: the strengthening of legal understanding and knowledge, the effectiveness of case-based learning, increased awareness of rights and obligations and a supportive attitude toward fair law enforcement, strengthened critical thinking and anti-hoax legal literacy, and the concrete application of legal values in daily life. This study confirms that civic legal literacy is formed through a graduated process from knowledge to legal behavior, and that case-based learning proves to be an effective key strategy, although the complexity of legal language and limited field practice experience remain challenges that require attention